The Neuroform Atlas stent to assist coil embolization of intracranial aneurysms: a multicentre experience - Ulfert, Christian; Pham, Mirko; Sonnberger, Michael; Amaya, Franco; Trenkler, Johannes; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2018)
Objective To assess the clinical safety and efficacy of the Atlas microstent in stent-assisted coil embolization of wide-necked intracranial aneurysms. - Methods Single-center observational study in 36 patients (24 female, 12 male, mean age 56 years) with 37 aneurysms for the endovascular treatment of wide-necked aneurysms. After giving informed consent, patients were included according to the following criteria: aneurysm dome-to-neck ratio <2 or neck diameter >4 mm, and a parent vessel diameter of ≤4.5 mm. Primary endpoint for clinical safety was absence of death, absence of major or minor stroke, and absence of transient ischemic attack. Primary endpoint for treatment efficacy was complete angiographic occlusion according to the Raymond-Roy occlusion classification (RROC) immediately after the procedure. - Results In 36/37 (97%) cases, the primary endpoint of safety was reached, one patient had a transitory ischemic attack which completely resolved until discharge. In 31/37 (84%) cases, complete occlusion (RROC 1) was reached, and in 6/36 (17%), a residual neck remained (RROC 2). A sequential approach (first stent, then coiling through the same catheter) was used in 21 cases; the other 16 were treated with the jailing technique. Deployment was technically successful in all cases. Follow-up at a median of 6.1 months was available for 29/37 (78%) aneurysms and showed complete occlusion in 27/29 aneurysms (93%) and a neck remnant in 2 cases (7%). - Conclusion Deployment of the Neuroform Atlas microstent is a safe and effective method for the treatment of intracranial wide-necked aneurysms.